Nisin and Nisin Probiotic Disrupt Oral Pathogenic Biofilms and Restore Their Microbiome Composition towards Healthy Control Levels in a Peri-Implantitis Setting - Allan Radaic; Hanna Brody; Fernando Contreras; Maryam Hajfathalian; Luke Lucido; Pachiyappan Kamarajan; Yvonne L. Kapila (Microorganisms, 2022)
Peri-implantitis is characterized by chronic inflammation of the peri-implant supporting tissues that progressively and irreversibly leads to bone loss and, consequently, implant loss. Similar to periodontal disease, oral dysbiosis is thought to be a driver of peri-implantitis. However, managing peri-implantitis with traditional treatment methods, such as nonsurgical debridement or surgery, is not always successful. Thus, novel strategies have been proposed to address these shortcomings. One strategy is the use of probiotics as antimicrobial agents since they are considered safe for humans and the environment. Specifically, the probiotic Lactococcus lactis produces nisin, which has been used worldwide for food preservation. The objective of this study was to determine whether nisin and the wild-type (WT) nisin-producing L. lactis probiotic can disrupt oral pathogenic biofilms and promote a healthier oral microbiome within these oral biofilms on titanium discs. Using confocal imaging and 16S rRNA sequencing, this study revealed that nisin and WT L. lactis probiotic disrupt oral pathogenic biofilms in a peri-implantitis setting in vitro. More specifically, nisin decreased the viability of the pathogen-spiked biofilms dose-dependently from 62.53 ± 3.69% to 54.26 ± 3.35% and 44.88 ± 2.98%, respectively. Similarly, 105 CFU/mL of WT L. lactis significantly decreased biofilm viability to 52.45 ± 3.41%. Further, both treatments shift the composition, relative abundance, and diversity levels of these biofilms towards healthy control levels. A total of 1 µg/mL of nisin and 103 CFU/mL of WT L. lactis were able to revert the pathogen-mediated changes in the Proteobacteria (from 80.5 ± 2.9% to 75.6 ± 2.0%, 78.0 ± 2.8%, and 75.1 ± 5.3%, respectively) and Firmicutes (from 11.6 ± 1.6% to 15.4 ± 1.3%, 13.8 ± 1.8%, and 13.7 ± 2.6%, respectively) phyla back towards control levels. Thus, nisin and its nisin-producing L. lactis probiotic may be useful in treating peri-implantitis by promoting healthier oral biofilms, which may be useful for improving patient oral health.